SISTEM APLIKASI BOOKING IN SERVICE PADA BENGKEL MOBIL ASRI BERBASIS ANDROID (Information Technology and Telematics, 2015)
Abstract : Needs service / repair routine on a car repair shop is a step or process that should not be overlooked for car owners. Started driving comfort of the car healthy and worthy life. Thus, in the auto repair business whether mild or severe, usually entrusted to a car repair shop subscription. Good quality of service workshop characterized by many customers in the auto repair shop. With so many car customers make the car owners have to wait queue turn his car service. This research aims to make application booking service on a car repair shop Asri that all customers can be served well. This application can be used to help customers who have android smartphones make it easier to communicate with the Workshop. Confirmation process the replacement / purchase of spare parts has been done through SMS and telephone, in this application there is a form for confirmation from the workshop to the car owner.   Kata Kunci : Booking Service, Bengkel Asri, Android.